Characterization of Leptin and Leptin Receptor Gene in the Siberian Sturgeon (Acipenser baerii): Molecular Cloning, Tissue Distribution, and Its Involvement in Feeding Regulation - Hongwei Wu; Jiamei Li; Kezhen Jiang; Yingzi Li; Zhaoxiong Yu; Bin Wang; Bo Zhou; Xin Zhang; Ni Tang; Zhiqiong Li (International Journal of Molecular Sciences, 2025)
Leptin is an adipokine known as a regulator of feeding and metabolism in mammals. Previous studies on fish have revealed its role in food intake regulation in limited teleosts. However, its specific function in Siberian sturgeon, an ancient Chondrostei fish, remains poorly understood. This study represents the first successful cloning of sequences for leptin and leptinreceptors in Siberian sturgeon, achieved using RT-PCR. The predicted leptin sequence in this species consists of 168 amino acids that exhibit low identity with other fish species, except within the Acipenseriformes order. Tissue distribution analysis revealed a high expression of Siberian sturgeon leptin mRNA in the liver and lepr mRNA in the hypothalamus. Fasting differentially affected the expression of leptin and lepr mRNA, with decreased levels in the hypothalamus and increased levels in the liver (leptin: 3–15 days; lepr: 6–15 days). Recombinant Siberian sturgeon leptin (Ssleptin) was produced via E. coli expression, and intraperitoneal injection (100 ng/g BW) significantly inhibited food intake. The anorectic effect was correlated with changes in hypothalamic gene expression, including downregulation of orexigenic factors (agrp, orexin, npy, and ghrelin) and upregulation of anorexigenic factors (pomc, mch, and insulin). Meanwhile, the peripheral administration of Ssleptin promoted the expression of resistin in the liver and concurrently increased cck and pyy mRNA levels in the valvular intestine. Furthermore, Ssleptin injection stimulated the expression of hypothalamic lepr, jak2, akt, and ampkα2 mRNA. These findings suggest that leptin plays a significant role in the feeding control of Siberian sturgeon and provide new insights into the evolutionary function of leptin in fish.